The Impact of the COVID-19 Emergency on the Quality of Life of the General Population - Roccella, Michele (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
COVID-19 is a pandemic that has forced many states to declare restrictive measures in order to prevent its wider spread. These measures are necessary to protect the health of adults, children, and people with disabilities.Long quarantine periods could cause an increase in anxiety crises, fear of contagion, and post-traumatic stress disorder (frustration, boredom, isolation, fear, insomnia, and difficulty concentrating).Post-traumatic stress disorder (PTSD) is a condition that can develop in subjects who have witnessed a traumatic, catastrophic, or violent event, or who have become aware of a traumatic experience that happened to a loved one.In fact, from current cases, it emerges that the prevalence of PTSD varies from 1% to 9% in the general population and can reach 50%-60% in subgroups of subjects exposed to traumas considered particularly serious. PTSD develops as a consequence of one or more physical or psychological traumatic events, such as exposure to natural disasters such as earthquakes, fires, floods, hurricanes, tsunamis; wars, torture, death threats; road accidents, robbery, air accidents; diseases with unfavorable prognoses; complicated or traumatic mourning; physical and sexual abuse and abuse during childhood; or victimization and discrimination based on gender, sexual orientation, or gender identity. It can also develop following changes in lifestyle habits caused by the COVID-19 epidemic.Thank you for reading the manuscripts in this Special Issue, "The Impact of the COVID-19 Emergency on the Quality of Life of the General Population".